2017
DOI: 10.1093/annonc/mdw536
|View full text |Cite
|
Sign up to set email alerts
|

Common breast cancer risk alleles and risk assessment: a study on 35 441 individuals from the Danish general population

Abstract: Common breast cancer risk alleles are associated with incidence and mortality of breast cancer in the general population, but not with other cancers. After including breast cancer allele sum in risk assessment, 25% of women currently being offered screening mammography had an absolute 5-year risk below the cutoff of average risk for a 50-year-old woman.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Another prospective study also reported no association between other types of cancer and a sum of breast cancer risk alleles at 72 loci. 29 Because we only analyzed all other tumors combined, we cannot exclude that the PRS 313 has an association with one specific type of other cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Another prospective study also reported no association between other types of cancer and a sum of breast cancer risk alleles at 72 loci. 29 Because we only analyzed all other tumors combined, we cannot exclude that the PRS 313 has an association with one specific type of other cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Modification of risk estimates by PRS-based stratification has been shown in a variety of clinical settings, including women who carry a pathogenic variant, high-risk women, and population cohorts. 11 , 15 - 17 These novel tools, however, are of particular interest to women who present for genetic risk assessment with increased risk due to a FH of breast cancer. FH and susceptibility variants contribute independently to risk prediction, yet the approximately 13% reduction in the OR for FH when adjusted for the PRS77 (or PRS313) indicates an overlapping contribution to risk.…”
Section: Discussionmentioning
confidence: 99%
“…Previous population-based health studies in Denmark have primarily focused on urbanized populations. This is the case for the Diet, Cancer and Health study recruiting participants from Copenhagen and Aarhus [16], the Copenhagen City Heart Study [17] and the Copenhagen General Population Study [19]. To make research findings generalizable for the general public and use the results in public-health planning and precision medicine, these studies do not only need to be large, but also represent the underlying diversity in the population.…”
Section: Discussionmentioning
confidence: 99%
“…The burden of diseases in the Lolland-Falster population is hypothesized to result from a combination of socioeconomic, genetic, lifestyle-related, familial and environmental factors, and the combination and weight of these factors are expected to differ from the pattern seen in previous studies of populations in the capital and larger cities of Denmark [17][18][19].…”
Section: Hypothesismentioning
confidence: 99%
See 1 more Smart Citation